Foreclosure Mitigation Efforts in the United States : Approaches and Challenges - Klyuev, Vladimir (IMF Staff Position Notes; Staff Position Note ;, 2009)
Home foreclosure rates have risen in the United States to the highest levels since the Great Depression. With house prices falling, lending standards tightening, unemployment rising, and interest rate resets in the pipeline, foreclosures are projected to go even higher. While most of the time a foreclosure is a suboptimal resolution of a distressed mortgage, a number of features of the mortgage finance system often prevent loan modifications. This paper reviews the impediments to successful mortgage restructuring and proposes a number of ways to improve the situation. The proposals build on the recognition that the key problem is a combination of negative housing equity and unaffordable debt service, and a successful loan modification scheme should address both issues. Given the key role foreclosures play in the adverse housing market dynamics, and several market failures that the paper identifies, the burden of mortgage debt restructuring should be shared by the taxpayer.